2009
DOI: 10.1159/000200767
|View full text |Cite
|
Sign up to set email alerts
|

Item Reduction of the Voice Handicap Index Based on the Original Version and on European Translations

Abstract: Objective: Constructing an internationally applicable short-scale of the Voice Handicap Index (VHI). Methods: Subjects were 1,052 patients with 5 different types of voice disorder groups from Belgium, France, Sweden, Germany, Italy, The Netherlands, Portugal, and the USA. Different 9- and 12-item subsets were selected from the 30 VHI items using (1) the first factor of an unrotated factor analysis (narrow range subsets) and (2) the first three factors after promax rotation (broad range subsets). Country-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 30 publications
(24 reference statements)
4
34
0
4
Order By: Relevance
“…The levels of reliability and internal consistency are in agreement with the original study by Jacobson et al [5] and those reported in most other studies using other language versions of the VHI [5,11,12,15,16,18]. Likewise, we observed high correlations between the 3 subdomains as well as between the subdomains and the total score of VHI both among patients and controls, suggesting that all three of the subscales mainly reflect one entity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The levels of reliability and internal consistency are in agreement with the original study by Jacobson et al [5] and those reported in most other studies using other language versions of the VHI [5,11,12,15,16,18]. Likewise, we observed high correlations between the 3 subdomains as well as between the subdomains and the total score of VHI both among patients and controls, suggesting that all three of the subscales mainly reflect one entity.…”
Section: Discussionsupporting
confidence: 92%
“…The abbreviated scales as published by Nawka et al [18] and Rosen et al [19] were calculated. ROC statistics were calculated employing the shortened total indices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is about functionally simple protocols, easy to apply, which have clear questions, thus becoming clinical tools for the assessment of treatment results. Also, provide more refined understanding of the dimensions of the effects of a voice problem in the patient's life and their psychosocial consequences, through selfawareness about their dysphonia, despite criticism on its preparation 1,4,9,[11][12][13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%